The Correlation Between Students’ Behavioral Engagement And Students’ Speaking Skill - Delis Meta Tiana; Retno Rahayuningsih (Wanastra: Jurnal Bahasa dan Sastra, 2022)
The objective of the research is to find out whether there is any correlation between students’ behavioral engagement and students’ speaking skill. The research used quantitative approach and the method was correlational research. The population was the eighth-grade students of SMP Islam Malahayati Jakarta. The sample of 26 students were randomly selected. The data of the students’ behavioral engagement were collected by using the questionnaire which was adopted from Miserandino’s BEQ, while the data of students’ speaking skill were collected by using the speaking test which had been validated by the expert judgment. The result shows that there is a positive significant correlation between students’ behavioral engagement and their speaking skill. It can be proven from the result of rxy = 0.698 is higher than rtable = 0.388 and tcount = 4.770 is higher than ttable = 1.7109. Coefficient determination shows that (0.698)2×100% = 48.72% so that students’ behavioral engagement contributes 48.72% towards their speaking skill. It can be concluded that there is a positive significant correlation between students’ behavioral engagement and students’ speaking skill. It means that the students who engage behaviorally have good speaking skill and vice versa.